Influence of Gestational Age at Initiation of Antihypertensive Therapy: Secondary Analysis of CHIPS Trial Data (Control of Hypertension in Pregnancy Study). Issue 6 (June 2018) - Pels, Anouk; Mol, Ben Willem J.; Singer, Joel; Lee, Terry; von Dadelszen, Peter; Ganzevoort, Wessel; Asztalos, Elizabeth; Magee, Laura A.; Gafni, Amiram; Gruslin, Andrée; Helewa, Michael; Hutton, Eileen; et al.
Abstract : For hypertensive women in CHIPS (Control of Hypertension in Pregnancy Study), we assessed whether the maternal benefits of tight control could be achieved, while minimizing any potentially negative effect on fetal growth, by delaying initiation of antihypertensive therapy until later in pregnancy. For the 981 women with nonsevere, chronic or gestational hypertension randomized to less-tight (target diastolic blood pressure, 100 mm Hg), or tight (target, 85 mm Hg) control, we used mixed-effects logistic regression to examine whether the effect of less-tight (versus tight) control on major outcomes was dependent on gestational age at randomization, adjusting for baseline factors as in the primary analysis and including an interaction term between gestational age at randomization and treatment allocation. Gestational age was considered categorically (quartiles) and continuously (linear or quadratic form), and the optimal functional form selected to provide the best fit to the data based on the Akaike information criterion. Randomization before (but not after) 24 weeks to less-tight (versus tight) control was associated with fewer babies with birth weight <10th centile ( P interaction =0.005), but more preterm birth ( P interaction =0.043), and no effect on perinatal death or high-level neonatal care >48 hours ( P interaction =0.354). For the mother, less-tight (versus tight) control was associated with more severe hypertension at all gestational ages but particularly so before 28 weeks ( P interaction =0.076). In women with nonsevere, chronic, or gestational hypertension, there seems to be no gestational age at which less-tight (versus tight) control is the preferred management strategy to optimize maternal or perinatal outcomes. Clinical Trial Registration—: URL:https://www.isrctn.com . Unique identifier: ISRCTN71416914. Abstract : Supplemental Digital Content is available in the text.